Organizational commitment level amongst Iraqis’ boxing coaches: survey study - Allami, FathilBakirMutsher; Mohammed, Laith Ali; Aseen, Mustafa Ismail (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to disclose level of organizational commitment amongst Iraqi’s boxing coaches. To achieve this aim study adopted descriptive research design andselected sample bypurposive sample technique, the sample included 53 coaches. Organizational commitment examined by questionnaire created in Iraqi environment. Results according to frequency and means value have showed the majority of sample have low and very low level of organizational commitment. In order to enhance coaches’ organizational commitment study recommended review regulations into force and reschedule programs and financial plans.